2009
DOI: 10.1111/j.1476-5381.2009.00438.x
|View full text |Cite|
|
Sign up to set email alerts
|

Transient receptor potential ankyrin receptor 1 is a novel target for pro‐tussive agents

Abstract: Background and purpose:The transient receptor potential ankyrin receptor 1 (TRPA1) is a cation channel, co-expressed with the pro-tussive transient receptor potential vanilloid type 1 (TRPV1) channel in primary sensory neurons. TRPA1 is activated by a series of irritant exogenous and endogenous a,b-unsaturated aldehydes which seem to play a role in airway diseases. We investigated whether TRPA1 agonists provoke cough in guinea pigs and whether TRPA1 antagonists inhibit this response. Experimental approach: Ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 48 publications
3
113
2
1
Order By: Relevance
“…45 Indeed, recent data from our laboratory have shown that the TRPA1-selective agonists acrolein and cinnamaldehyde induce coughing in guinea pigs and human volunteers, respectively. 45 This fi nding has been confi rmed by Andrè and colleagues, 46 who stimulated coughing in guinea pigs with aerosolized TRPA1-selective agonists and subsequently demonstrated inhibition of these responses with both selective and nonselective TRPA1 blockers. In addition, cigarette smoke-induced cough in guinea pigs can also be partially ( ‫ف‬ 50%) inhibited by HC-030031.…”
Section: Trpa1 and Coughmentioning
confidence: 74%
See 1 more Smart Citation
“…45 Indeed, recent data from our laboratory have shown that the TRPA1-selective agonists acrolein and cinnamaldehyde induce coughing in guinea pigs and human volunteers, respectively. 45 This fi nding has been confi rmed by Andrè and colleagues, 46 who stimulated coughing in guinea pigs with aerosolized TRPA1-selective agonists and subsequently demonstrated inhibition of these responses with both selective and nonselective TRPA1 blockers. In addition, cigarette smoke-induced cough in guinea pigs can also be partially ( ‫ف‬ 50%) inhibited by HC-030031.…”
Section: Trpa1 and Coughmentioning
confidence: 74%
“…In addition, cigarette smoke-induced cough in guinea pigs can also be partially ( ‫ف‬ 50%) inhibited by HC-030031. 46 It may be that the tussive response remaining may be mediated by activation of neuronal nicotinic acetylcholine receptors, as a role for these receptors has been identifi ed in cigarette smoke-induced cough in normal volunteers. 47 That TRPA1 has been identifi ed as a pro-tussive receptor in both clinical trials and a guinea Figure 2.…”
Section: Trpa1 and Coughmentioning
confidence: 99%
“…Jugular C-fibers terminate throughout the extrapulmonary and intrapulmonary airways while nodose Cfibers sparsely innervate the extrapulmonary airways (26). Stimuli that activate both nodose and jugular ganglia C-fibers in guinea pigs readily evoke coughing when delivered as aerosols to conscious guinea pigs (1,4,6,9,12,18). Which of these C-fiber subtypes drive the cough reflex in conscious guinea pigs has not previously been determined.…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1 antagonists have been demonstrated to inhibit sensory nerve activation and cough evoked by TRPA1 agonists and inflammatory mediators such as PGE 2 and bradykinin following activation of their respective GPCRs and cough in response to citric acid (low pH solution) [23,[61][62][63][64]. Cinnamaldehyde, a TRPA1 agonist, has been shown to cause cough in clinical studies in normal volunteers [63].…”
Section: Trpa1mentioning
confidence: 99%